1998
DOI: 10.1023/a:1022458928442
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study aimed at determining the effect of drug therapy, age and type of dementia on biological markers. Both platelet monoamine oxidase type B (MAO-B) activity and serotonin content of 57 demented patients and 20 control subjects were determined. Platelet MAO-B activity was measured using [14C]tyramine as substrate. Serotonin content was determined by HPLC-EC method. Increased platelet serotonin content and platelet count was found in patients with dementia compared to controls. A positive correlation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…These AD-related findings were subsequently confirmed in at least 12 clinical studies from different research groups [57, 59, 73, 112120]. Five other studies, however, reported no AD-related activity increase [58, 61, 73, 99, 121]. Importantly, instead of phenethylamine, three of these studies used the substrates tyramine or kynuramine [61, 73, 99], both converted by Mao-A and Mao-B [122].…”
Section: Reviewmentioning
confidence: 57%
See 4 more Smart Citations
“…These AD-related findings were subsequently confirmed in at least 12 clinical studies from different research groups [57, 59, 73, 112120]. Five other studies, however, reported no AD-related activity increase [58, 61, 73, 99, 121]. Importantly, instead of phenethylamine, three of these studies used the substrates tyramine or kynuramine [61, 73, 99], both converted by Mao-A and Mao-B [122].…”
Section: Reviewmentioning
confidence: 57%
“…Higher Mao-B activity in patient samples could only be detected with the Mao-B-specific substrate phenethylamine. These AD-related findings were subsequently confirmed in at least 12 clinical studies from different research groups [57, 59, 73, 112120]. Five other studies, however, reported no AD-related activity increase [58, 61, 73, 99, 121].…”
Section: Reviewmentioning
confidence: 61%
See 3 more Smart Citations